Superficial-type endobronchial metastases from colon cancer: A case report - KURISHIMA, KOICHI (D.A. Spandidos, 2014)
Certain internal malignancies, including colon cancer, can develop endobronchial metastasis. The present study reports a case of colon cancer with superficial-type endobronchial metastases in a 76-year-old male. Chest computed tomography revealed small masses and infiltrates in each lung, with bilateral hilar lymph node swelling. Superficial endobronchial tumors in each of the bronchi were unexpectedly found by bronchoscopic examination. A biopsy specimen obtained from the endobronchial tumor was diagnosed as colon cancer. Superficial-type endobronchial metastasis from colon cancer is extremely rare, however, such metastasis should be considered for patients who have a history of colon cancer. There should be no hesitation in performing a bronchoscopic biopsy as an additional examination.